Infusing disability awareness in educational settings through reverse integration: Exploring students` knowledge and perceptions of disability and inclusion in wheelchair basketball - Oldroyd, R. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction: Students` knowledge and learning experiences within the field of sport, exercise and adapted physical activity will contribute to promoting physical activity and facilitate inclusive opportunities for disabled people. It is necessary for researchers and educators to understand and expand pedagogical approaches on how students acquire learning experiences and knowledge. By applying reverse integration, this paper explores a set of learning practices that can be considered and adapted in an educational setting. Through a collaborative design of practice between academic tutors and the lead researcher, the aim was to enhance students` knowledge and understanding of disability and inclusion. Methods: The context of this study is a short educational course informed by disability studies perspectives focused on reverse integration. A qualitative analysis of the meanings from students` engagement and experience in a disability awareness workshop focused on reverse integration in wheelchair basketball. Fifty-three students were invited to attend a workshop which coincided with their module delivery and assessment at university. The students were invited to attend a lecture, a practical and a seminar across two days while actively engaging with national wheelchair basketball athletes. Questionnaires and informal recorded discussions were used to gain responses. A content analysis was conducted and reviewed, and all patterns, commonalities and student perceptions were noted. Results: The data indicate that students before the course had limited knowledge and disability awareness in wheelchair basketball. During the course, the students found the practical element/reverse integration, by taking part in a wheelchair basketball session, had helped them to become more aware and have a sense of appreciation towards people who use a wheelchair daily and the strength that it involves to perform certain skills. After the course, once all lectures and practical`s had taken place, the students shared they had gained much more knowledge about disabilities and overall felt more confident to work with, and engage with disabled athletes. Lastly, most students found that it was an invaluable experience and expressed that there should be more sports that include able-bodied and disabled people together as it helps to minimise and address certain barriers towards sport participation. Discussion: In analysing the data it was apparent that the students expressed a meaningful shift in their thinking and their value of performance ability of disabled athletes and disability sports was much more of an appreciation towards their thinking around disabilities in sport. As a result, from the workshop, reverse integration in wheelchair basketball has contributed to changing perceptions of players with disabilities and their understanding of disabilities and inclusion. These insights have the capacity to influence educational settings and coach education pathways.